Development of an Adolescent Mental Health Scale Based on the Mentalkusehat.com Digital Platform - Bambang Setyawan; Arief Rahman Yusuf; Sigit Dwi Laksana (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Adolescent mental health is a critical concern in school guidance and counseling services; however, valid and reliable digital self-screening instruments remain limited in the Indonesian context. This study aimed to develop and validate a digital adolescent mental health scale, adapted from the Depression Anxiety Stress Scales–21 (DASS-21), and to integrate it into the mentalkusehat.com platform. Instrument development followed Azwar’s eight-stage psychological scale-construction model and was tested with 150 senior high school students. Content validity showed excellent results, with Item-Level Content Validity Index (I-CVI) and Scale-Level Content Validity Index (S-CVI/Ave) values of 1.00. Construct validity was examined using Confirmatory Factor Analysis (CFA), supporting a three-factor model (stress, anxiety, and depression) with acceptable fit indices (CFI = 0.939; TLI = 0.930; RMSEA = 0.067). Internal consistency was high, with Cronbach’s alpha values exceeding 0.80 across subscales. Platform feasibility evaluation using the ACTIONS model yielded a score of 92.86%, categorized as highly feasible. These findings support the instrument’s usefulness for early detection and need assessment in school counseling services and contribute to the digitalization of adolescent mental health assessment in Indonesia. Keywords: adolescent mental health, DASS-21, digital assessment, guidance and counseling, validity and reliability